Albania : Poverty Reduction Strategy Paper-National Strategy for Development and Integration. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper focuses on the Poverty Reduction Strategy Paper-National Strategy for Development and Integration (PRSP-NSDI) for Albania. The paper provides an overview of the key challenges facing the country. It presents a brief statement of the national vision, identifies the strategic priorities, and articulates the strategic goals to be achieved. The paper also summarizes the key points of each of the underlying strategies by strategic priority, and discusses the main changes in the distribution of resources across broad sectors that will be needed in the period 2007-13.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet